The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/ni.3635
|View full text |Cite
|
Sign up to set email alerts
|

1st International Conference on Human & Translational Immunology

Abstract: The 1st International Conference on Human &Translational Immunology convened in Rhodes, Greece, and provided a venue for stimulating scientific discussions on the human immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Yet despite such understanding of the functions elicited by distinct DC subsets (5), our knowledge of the DC subset or subsets that promote the most potent antitumor responses in humans is less clear. We previously reported that migratory skin CD5 + DCs, which we found on a subset of DC2s, prime inflammatory T H cells and multifunctional CTLs more effectively than their CD5 -DC2 counterparts (18,20). Their increased frequency in inflammatory settings led us to hypothesize that these cells are predominantly involved in the antitumor response.…”
Section: Resultsmentioning
confidence: 75%
“…Yet despite such understanding of the functions elicited by distinct DC subsets (5), our knowledge of the DC subset or subsets that promote the most potent antitumor responses in humans is less clear. We previously reported that migratory skin CD5 + DCs, which we found on a subset of DC2s, prime inflammatory T H cells and multifunctional CTLs more effectively than their CD5 -DC2 counterparts (18,20). Their increased frequency in inflammatory settings led us to hypothesize that these cells are predominantly involved in the antitumor response.…”
Section: Resultsmentioning
confidence: 75%